Religious service attendance and lower depression among women - a prospective cohort study - Li, Shanshan (Ann Behav Med, 2016)
OBJECTIVE: Previous studies on the association between religious service attendance and depression have been mostly cross-sectional, subject to reverse causation, and did not account for the potential feedback between religious service attendance and depression. We prospectively evaluated whether religious service attendance decreased risk of subsequent risk of depression and whether depression increased subsequent cessation of service attendance, while explicitly accounting for feedback with potential effects in both directions. METHOD: We included a total of 48,984 U.S. nurses who were participants of the Nurses’ Health Study with mean age 58 years and who were followed up from 1996 to 2008. Religious services attendance was self-reported in 1992, 1996, 2000, and 2004. Depression was defined as self-reported physician-diagnosed clinical depression, regular anti-depressant use, or severe depressive symptoms. Multivariate logistic regression and marginal structural models were used to estimate the odds ratio of developing incident depression, adjusted for baseline religious service attendance, baseline depression and time-varying covariates. RESULTS: Compared with women who never attended services, women who had most frequent and recent religious service attendance had the lowest risk of developing depression (odds ratio [OR] =0.71, 95% confidence interval [CI]:0.62–0.82). Compared with women who were not depressed, women with depression were less likely to subsequently attend religious services once or more per week (OR=0.74, 95% CI: 0.68–0.80). CONCLUSIONS: In this study of U.S. women, there is evidence that higher frequency of religious service attendance decreased the risk of incident depression and women with depression were less likely to subsequently attend services.